An approach to help differentiate postinfarct scar from borderzone tissue using Ripple Mapping during ventricular tachycardia ablation. (12th January 2023) - Khanra, Dibbendhu; Calvert, Peter; Hughes, Susan; Waktare, Johan; Modi, Simon; Hall, Mark; Todd, Derick; Mahida, Saagar; Gupta, Dhiraj; Luther, Vishal
Abstract: Background: Ventricular scar is traditionally highlighted on a bipolar voltage (BiVolt) map in areas of myocardium <0.50 mV. We describe an alternative approach using Ripple Mapping (RM) superimposed onto a BiVolt map to differentiate postinfarct scar from conducting borderzone (BZ) during ventricular tachycardia (VT) ablation. Methods: Fifteen consecutive patients (left ventricular ejection fraction 30 ± 7%) underwent endocardial left ventricle pentaray mapping (median 5148 points) and ablation targeting areas of late Ripple activation. BiVolt maps were studied offline at initial voltage of 0.50–0.50 mV to binarize the color display (red and purple). RMs were superimposed, and the BiVolt limits were sequentially reduced until only areas devoid of Ripple bars appeared red, defined as RM‐scar. The surrounding area supporting conducting Ripple wavefronts in tissue <0.50 mV defined the RM‐BZ. Results: RM‐scar was significantly smaller than the traditional 0.50 mV cutoff (median 4% vs. 12% shell area, p < .001). 65 ± 16% of tissue <0.50 mV supported Ripple activation within the RM‐BZ. The mean BiVolt threshold that differentiated RM‐scar from BZ tissue was 0.22 ± 0.07 mV, though this ranged widely (from 0.12 to 0.35 mV). In this study, septal infarcts (7/15) were associated with more rapid VTs (282 vs. 347 ms, p = .001), and had a greater proportion of RM‐BZ to RM‐scar (median ratio 3.2 vs. 1.2, p = .013) with faster RM‐BZ conduction speed (0.72 vs. 0.34 m/s, p = .001). Conversely, scars that supported hemodynamically stable sustained VT (6/15) were slower (367 ± 38 ms), had a smaller proportion of RM‐BZ to RM‐scar (median ratio 1.2 vs. 3.2, p = .059), and slower RM‐BZ conduction speed (0.36 vs. 0.63 m/s, p = .036). RM guided ablation collocated within 66 ± 20% of RM‐BZ, most concentrated around the RM‐scar perimeter, with significant VT reduction (median 4.0 episodes preablation vs. 0 post, p < .001) at 11 ± 6 months follow‐up. Conclusion: Postinfarct scars appear significantly smaller than traditional 0.50 mV cut‐offs suggest, with voltage thresholds unique to each patient.